P330 Ultrasound remission after biologic induction predicts long-term endoscopic remission in Crohn's disease. (30th January 2023) - Allocca, M; Dell'Avalle, C; Furfaro, F; Zilli, A; Radice, S; D'Amico, F; Peyrin-Biroulet, L; Fiorino, G; Danese, S
Abstract: Background: Intestinal ultrasound (IUS) is accurate and non-invasive to detect and monitor disease activity in Crohn's disease (CD). The Bowel Ultrasound Score (BUSS= 0.75 × bowel wall thickness + 1.65 × presence (1) or absence (0) of bowel wall flow) demonstrated high accuracy in detecting therapy-related changes, and good correlation with the Simple Endoscopic Score for CD (SES-CD). The most accurate cutoff value for BUSS was 3.52 for endoscopic remission (SES-CD ≤ 2).This study aimed to prospectively evaluate ultrasound remission as a relevant treatment target. Methods: Consecutive patients with active CD (SES-CD > 2) starting biologic treatments were included. Patients underwent colonoscopy and IUS at baseline and after 1 year of treatment. Clinical, biochemical and ultrasound assessments were additionaly performed at week 12. Primary outcome was to evaluate whether ultrasound remission at week 12 could predict endoscopic remission at week 54. Endoscopic remission was defined as SES-CD ≤ 2, ultrasound remission was defined by BUSS ≤ 3.52, clinical remission was defined by HBI (Harvey-Bradshaw Index) < 5, and biochemical remission was defined by normalization of C-reactive protein (< 5 mg/L) and fecal calprotectin (three different thresholds were assessed: < 250 µg/g, < 100 µg/g, < 50 µg/g). Results: Ninety-three patients were included (8 under infliximab, 40 under adalimumab, 5 under vedolizumab and 40 under ustekinumab). Eighteen patients (19%) and 36 patients (39%) achieved endoscopic remission and ultrasound remission at week 54, respectively. CD patients with ultrasound remission at week 12 were more likely to achieve endoscopic remission (odds ratio [OR] 6.88 [2.14–22.04]; p = 0.001) and ultrasound remission (OR 4.26 [1.61–11.24]; p = 0.003) at week 54. Calprotectin value < 50 µg/g at week 12 predicted endoscopic remission at univariable (OR 3.14 [1.04–9.45]; p = 0.041), but not at multivariable analysis. No other clinical or biochemical variables at week 12 predicted endoscopic and/or ultrasound remission at week 54. Conclusion: Ultrasound remission achieved at week 12 may predict long-term endoscopic remission and may be a strategic treatment target, both in clinical practice and in clinical trials.